Cadmium(II) Schiff base Complex Containing 5-Fluoroisatin Moiety: Synthesis, Characterization, Antibacterial Activity and Structural Studies - Manan, Mohd Abdul Fatah Abdul; Cordes, David Bradford (Trends in Sciences, 2022)
The Schiff base ligand, HSB5FISA (H1), obtained by the condensation of S-benzyldithiocarbazate with 5-fluoroisatin, has been employed to synthesize a new cadmium(II) complex, Cd(SB5FISA)2 (2) (SB5FISA = monoanionic form of H1). The complex has been characterized by elemental analysis, molar conductivity, magnetic susceptibility, inductively coupled plasma atomic emission spectroscopy (ICP-AES), Fourier-transform infrared spectroscopy (FT-IR) and ultraviolet-visible spectroscopy (UV-Vis). The crystallographic study of Cd(SB5FISA)2×2DMSO (2a) (DMSO = dimethyl sulfoxide) was conducted using single-crystal X-ray diffraction. The crystal structure of 2a confirmed the presence of 6-coordinated cadmium in a distorted octahedral environment. Ligand H1 behaves in a tridentate monoanionic fashion, coordinating to a cadmium(II) metal centre through the thiolate sulfur, azomethine nitrogen and carbonyl oxygen. The antibacterial activity of both H1 and 2 was examined against 4 different bacterial strains using the disc diffusion method. Complex 2 showed significant inhibitory effect against Bacillus subtilis with an inhibition zone of 14 mm, comparable to the standard antibiotic streptomycin. HIGHLIGHTS Cd(II) complex of 5-fluoroisatin Schiff base was synthesized Structural studies of compound determined via single crystal X-ray diffraction Compound exhibited significant antibacterial activity towards Bacillus subtilis GRAPHICAL ABSTRACT